The Effect of Total Quality Management and Service Quality to Customer Satisfaction in the Store Feandra Cake Pekanbaru - Nofirda, Fitri Ayu; Ayu, Nadya Gusti; Binangkit, Intan Diane (Inovbiz: Jurnal Inovasi Bisnis, 2023)
Customer satisfaction is element important in developing a company to remain able to face business competition. Factors that can affect customer satisfaction are total quality management and service quality. This study aims to determine how much influence total quality management has on customer satisfaction and how much influence service quality has on customer satisfaction. The study used a quantitative approach with sampling techniques using purposive sampling through questionnaires distributed to customers at Feandra Cake Pekanbaru store as many as 130 respondents. The study used multiple linear regression analysis. The results of this study show that the relationship is positive and significant between total quality management and customer satisfaction. While on the independent variable, namely service quality, has a positive and significant relationship with the dependent variable, namely customer satisfaction.